2011
DOI: 10.1121/1.3596457
|View full text |Cite
|
Sign up to set email alerts
|

Active noise attenuation in ventilation windows

Abstract: The feasibility of applying active noise control techniques to attenuate low frequency noise transmission through a natural ventilation window into a room is investigated analytically and experimentally. The window system is constructed by staggering the opening sashes of a spaced double glazing window to allow ventilation and natural light. An analytical model based on the modal expansion method is developed to calculate the low frequency sound field inside the window and the room and to be used in the active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…However, the additional noise reduction due to the active control was found to be limited to below 5 dB, except at some individual frequencies, at which the noise reduction was above 10 dB. In addition, as in the study of Huang et al [69], noise reduction improvement could only be found at frequencies below the first gap mode cut-on.…”
Section: Plenum Windows/double-wall Structures With Staggered Air Inlmentioning
confidence: 64%
See 1 more Smart Citation
“…However, the additional noise reduction due to the active control was found to be limited to below 5 dB, except at some individual frequencies, at which the noise reduction was above 10 dB. In addition, as in the study of Huang et al [69], noise reduction improvement could only be found at frequencies below the first gap mode cut-on.…”
Section: Plenum Windows/double-wall Structures With Staggered Air Inlmentioning
confidence: 64%
“…Through the use of scale model experiments, Huang et al [69] showed that the control was only satisfactory at frequencies below the cut-on frequency of the first odd mode in the gap direction. They found that there was a 20 dB additional noise reduction when the active control was applied.…”
Section: Plenum Windows/double-wall Structures With Staggered Air Inlmentioning
confidence: 99%
“…The idea of active noise cancellation (ANC) as a possible solution for home window noise attenuation has been previously studied [3,[11][12][13]. In an ANC system, the control algorithm drives an actuator (e.g.…”
Section: Review Of Previous Research On Window Noise Controlmentioning
confidence: 99%
“…However, this solution is less effective in summer times or in southern countries where the windows need to be frequently opened. Several active noise control (ANC) systems have been applied to the open windows to solve this problem [1]- [3]. The systems were proved to reduce the transmitted exterior noise when the windows were open.…”
Section: Introductionmentioning
confidence: 99%
“…The systems were proved to reduce the transmitted exterior noise when the windows were open. Huang investigated the active window system that was constructed by staggering the opening sashes of a spaced double glazing window to allow ventilation and natural light [1]. Kwon proposed an active window system that consisted of reference sensors installed outside the room and control sources installed on the window frame.…”
Section: Introductionmentioning
confidence: 99%